2011
DOI: 10.5001/omj.2011.49
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Toxicity in Adults: A Case Series from an Area with Endemic Hypovitaminosis D

Abstract: Vitamin D deficiency state is endemic to the Kashmir valley of the Indian subcontinent. Physicians often treat patients with high doses of vitamin D for various ailments and on occasion the prescribed doses far exceed the requirements of the patients. Ten cases of hypercalcemia due to vitamin D intoxication are presented with features of vomiting, polyuria, polydipsia, encephalopathy and renal dysfunction. All the patients had demonstrable hypercalcemia and vitamin D levels were high in nine of the 10 cases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 19 publications
0
30
0
10
Order By: Relevance
“…Hypercalcemia and hypercalciuria induced with oral dihydrotachysterol, a synthetic vitamin D analog, in rats (92) and hypervitaminosis D in humans (50,53) are associated with polyuria. Activation of the Ca-sensing receptor by the hyper- calciuria may decrease vasopressin-induced water reabsorption (82) in the cortical collecting duct, although this purported mechanism is controversial (9).…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalcemia and hypercalciuria induced with oral dihydrotachysterol, a synthetic vitamin D analog, in rats (92) and hypervitaminosis D in humans (50,53) are associated with polyuria. Activation of the Ca-sensing receptor by the hyper- calciuria may decrease vasopressin-induced water reabsorption (82) in the cortical collecting duct, although this purported mechanism is controversial (9).…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, apresenta outras funções biológicas fundamentais na diferenciação celular, inibição do crescimento celular e modulação imune 2,3 .…”
Section: Discussionunclassified
“…1 A toxicidade da vitamina D, também chamada hipervitaminose D, é extremamente rara, potencialmente grave, e ocorre em doses mais elevadas. 1,2 As características clínicas da hipervitaminose D são decorrentes, principalmente, da hipercalcemia. 1,2 Diante de um quadro de vômitos persistentes e hipercalcemia, na presença de hormônio da paratireódide normal, o diagnóstico de intoxicação por vitamina D deve ser suspeitado e, a normalização de seus níveis alivia os sintomas e pode prevenir lesão renal aguda.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Case series by Koul PA et al found nine of ten cases of hypercalcaemia are due to Vitamin D toxicity. [11][12][13] In vitro pharmaceutical interactions are well known. In a nutraceutical combination, extent to which iron and calcium absorb and be beneficial to the patient is questionable.…”
Section: 9mentioning
confidence: 99%